Refractive Index Border Associated with Nonlinear Optical Properties in Superhybrid Transparent TiO2 Nanoparticles-Polymer: Great Potential for Ultrafast Optical Waveguide in Optical Communication - Hendry Izaac Elim (Faculty of Mathematics and Natural Sciences, University of Pattimura, 2020)
The excellency of a superhybrid material based TiO2 nanoparticles (NPs) has been improved by the surface modification of the TiO2 with a coupling agent of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane to render them highly compatible with organic monomer mixtures avoiding aggregation. Such TiO2 NPs are then attached with a polymer. The border of linear refractive index of hybrid TiO2 NPs-polymer is enhanced in comparison with that of pure epoxy resin or polymer. Nonlinear refractive index and nonlinear absorption coefficient of hybrid TiO2 NPs-polymer are measured by femtosecond Z-scan technique at 800 nm. This hybrid material has been fabricated and studied to have a great potential for ultrafast optical waveguide in optical communication quantified by the propagation loss of the hybrid TiO2 NPs-polymer optical waveguide in the range of 4.79 to 11.90 dB/cm, which is depending on the volume percent of TiO2 NPs